An unprecedented fully reduced MoV60 polyoxometalate: from an all-inorganic molecular light-absorber model to improved photoelectronic performance. Issue 16 (1st April 2022) - Li, Xue-Xin; Ji, Tuo; Gao, Jun-Yang; Chen, Wei-Chao; Yuan, Ye; Sha, Hao-Yan; Faller, Roland; Shan, Guo-Gang; Shao, Kui-Zhan; Wang, Xin-Long; Su, Zhong-Min
Abstract : An unprecedented fully reduced Mo V 60 POM served as a cheap and robust molecular light-absorber model possessing wide light absorption and was applied to build a co-sensitized solar cell photoelectronic device. Abstract : Fully reduced polyoxometalates are predicted to give rise to a broad and strong absorption spectrum, suitable energy levels, and unparalleled electronic and optical properties. However, they are not available to date. Here, an unprecedented fully reduced polyoxomolybdate cluster, namely Na8 [Mo V 60 O140 (OH)28 ]·19H2 O Mo V 60 , was successfully designed and obtained under hydrothermal conditions, which is rare and is the largest fully reduced polyoxometalate reported so far. The Mo V 60 molecule describes one Keggin ε-Mo12 encapsulated in an unprecedented Mo24 cage, giving rise to a double truncated tetrahedron quasi-nesting architecture, which is further face-capped by another four Mo6 tripods. Its crystalline stability in air, solvent tolerance, and photosensitivity were all shown. As a cheap and robust molecular light-absorber model possessing wide light absorption, Mo V 60 was applied to build a co-sensitized solar cell photoelectronic device along with N719 dyes and the optimal power conversion efficiency was 28% higher than that of single-dye sensitization. These results show that Mo V 60 polyoxometalate could serve as an ideal model for the design and synthesis of all-inorganic molecular light-absorbers for other light-driven processes in the future.